Preschool child growth attainment and velocity during an agriculture intervention in rural Panama may be diminished by soil-transmitted helminths - Rachel J. Krause; Rachel J. Krause; Marilyn E. Scott; Odalis T. Sinisterra; Kristine G. Koski (Frontiers Media S.A., 2023)
BackgroundAgricultural interventions are often recommended to address undernutrition in subsistence farming communities. However, intensified agriculture exposure can increase soil transmitted helminth (STH) infections, which are linked with poor child growth. This study examined impacts of the VERASAN public health and agricultural intervention program on preschool child growth attainment (HAZ and WAZ) and relative growth velocity over 7 months [change in height-for-age (∆HAD) and weight-for-age (∆WAD) difference].MethodsVERASAN was initiated in 15 subsistence farming communities in rural Panama experiencing chronic undernutrition. Activities targeted improved household food security, preschool child diets and growth by intensifying and diversifying household agriculture. Our objectives were to explore the relationship between VERASAN and preschool child growth attainment (HAZ and WAZ) and velocity (∆HAD and ∆WAD) during one agricultural cycle in 238 households. We compared those new to VERASAN with those involved for 1 or 5 years, and identified if agricultural practices, food security, diet diversity and treatment of pre-existing STH infection were associated with growth attainment or velocity.ResultsPrior participation in VERASAN did not directly influence WAZ, HAZ or ΔHAD but VERASAN-related benefits had an indirect influence. ΔHAD was positively associated with VERASAN-associated improvements in diet diversity and food security. HAZ and WAZ during land preparation were positively associated with diet diversity and HAZ with food security during harvest. HAZ was negatively associated with children visiting the agricultural plot, consuming leafy green vegetables and pre-existing hookworm infections. Both agricultural season and STH influenced ΔWAD. Children in VERASAN for 1 or 5 years experienced growth faltering between land preparation and growing season, but not those new to VERASAN. In contrast, between growing and harvest, ∆WAD declined in children new to VERASAN compared to children in VERASAN for longer. ΔWAD from land preparation to harvest was higher with pre-existing Ascaris infection whereas it was lower between growing season and harvest for pre-existing hookworm infection.ConclusionIn a context of preschool child growth faltering, malnutrition and STH infections, improved food security, agricultural production and diet diversity associated with VERASAN were associated with improved growth. In contrast, STH infections were negatively associated with some, but not all, growth outcomes.